Treatment of Moral Injury in U.S. Veterans with PTSD Using a Structured Chaplain Intervention - Ames, Donna (Journal of religion and health, 2021)
Moral injury is a complex phenomenon characterized by spiritual, psychological, and moral distress caused by actions or acts of omission inconsistent with an individual’s moral and ethical values. We present two cases from an ongoing randomized controlled trial of a spiritually integrated structured intervention delivered by chaplains for individuals suffering from moral injury. Chaplains met with Veterans for twelve 50-min sessions that each focused on a specific domain of moral injury. Participants were asked to complete validated scales assessing symptoms of moral injury and PTSD, including the PTSD Checklist for DSM-5 (PCL-5), Moral Injury Symptom Scale-Military Version Short Form, and Moral Injury Symptom Scale-Military Version Long Form. We report on two Veterans who completed the intervention and demonstrated significant improvement in moral injury and PTSD symptoms.